Development of Learning Tools Based on Hybrid-Creative Problem Solving (H-CPS) Strategy to Improve The Critical Thinking Skills of Prospective Physics Teachers - Sutrio, Sutrio; Busyairi, Ahmad; Susilawati, Susilawati; Gunawan, Gunawan; Nisrina, Nina; Zianturi, Elda Elfara (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to develop a learning device based on the Hybrid-Creative Problem Solving (H-CPS) Model to improve the critical thinking skills of prospective physics teachers. The development model refers to the 4D approach (Define, Design, Develop, and Disseminate). The learning devices developed include H-CPS learning design, learning videos, student worksheets, and critical thinking skills test instruments. The device validation process was carried out by three experts who are competent in their fields. The validation results showed that all devices were declared valid, although several minor suggestions for improvement had been accommodated. The research findings showed that the learning devices and test instruments developed had a high level of validity and reliability, and showed great potential in providing meaningful and effective learning experiences for students. Based on these results, this study recommends the implementation of limited trials or wider trials to ensure the effectiveness of their implementation before being disseminated and used more widely in higher education environments.